Get the answers you need at Westonci.ca, where our expert community is dedicated to providing you with accurate information. Discover detailed solutions to your questions from a wide network of experts on our comprehensive Q&A platform. Get quick and reliable solutions to your questions from a community of experienced experts on our platform.
Sagot :
Let’s solve the given system of equations step-by-step.
The given system of equations is:
[tex]\[ x + \frac{6}{y} - 7 = 0 \][/tex]
[tex]\[ 2xy + 4 = 10y \][/tex]
Step 1: Solve the first equation for [tex]\( x \)[/tex]
Rewrite the first equation as:
[tex]\[ x + \frac{6}{y} = 7 \][/tex]
Subtract [tex]\(\frac{6}{y}\)[/tex] from both sides:
[tex]\[ x = 7 - \frac{6}{y} \][/tex]
Step 2: Substitute [tex]\( x \)[/tex] from the first equation into the second equation
The second equation is:
[tex]\[ 2xy + 4 = 10y \][/tex]
Substitute [tex]\( x = 7 - \frac{6}{y} \)[/tex] into the second equation:
[tex]\[ 2\left(7 - \frac{6}{y}\right)y + 4 = 10y \][/tex]
Step 3: Simplify and solve for [tex]\( y \)[/tex]
Distribute [tex]\( y \)[/tex]:
[tex]\[ 2(7y - 6) + 4 = 10y \][/tex]
[tex]\[ 14y - 12 + 4 = 10y \][/tex]
Combine like terms:
[tex]\[ 14y - 8 = 10y \][/tex]
Subtract [tex]\( 10y \)[/tex] from both sides:
[tex]\[ 4y - 8 = 0 \][/tex]
Add 8 to both sides:
[tex]\[ 4y = 8 \][/tex]
Divide both sides by 4:
[tex]\[ y = 2 \][/tex]
Step 4: Substitute [tex]\( y \)[/tex] back into the expression for [tex]\( x \)[/tex]
[tex]\[ x = 7 - \frac{6}{y} \][/tex]
Substitute [tex]\( y = 2 \)[/tex]:
[tex]\[ x = 7 - \frac{6}{2} \][/tex]
[tex]\[ x = 7 - 3 \][/tex]
[tex]\[ x = 4 \][/tex]
Therefore, the solution to the system of equations is:
[tex]\[ (x, y) = (4, 2) \][/tex]
The given system of equations is:
[tex]\[ x + \frac{6}{y} - 7 = 0 \][/tex]
[tex]\[ 2xy + 4 = 10y \][/tex]
Step 1: Solve the first equation for [tex]\( x \)[/tex]
Rewrite the first equation as:
[tex]\[ x + \frac{6}{y} = 7 \][/tex]
Subtract [tex]\(\frac{6}{y}\)[/tex] from both sides:
[tex]\[ x = 7 - \frac{6}{y} \][/tex]
Step 2: Substitute [tex]\( x \)[/tex] from the first equation into the second equation
The second equation is:
[tex]\[ 2xy + 4 = 10y \][/tex]
Substitute [tex]\( x = 7 - \frac{6}{y} \)[/tex] into the second equation:
[tex]\[ 2\left(7 - \frac{6}{y}\right)y + 4 = 10y \][/tex]
Step 3: Simplify and solve for [tex]\( y \)[/tex]
Distribute [tex]\( y \)[/tex]:
[tex]\[ 2(7y - 6) + 4 = 10y \][/tex]
[tex]\[ 14y - 12 + 4 = 10y \][/tex]
Combine like terms:
[tex]\[ 14y - 8 = 10y \][/tex]
Subtract [tex]\( 10y \)[/tex] from both sides:
[tex]\[ 4y - 8 = 0 \][/tex]
Add 8 to both sides:
[tex]\[ 4y = 8 \][/tex]
Divide both sides by 4:
[tex]\[ y = 2 \][/tex]
Step 4: Substitute [tex]\( y \)[/tex] back into the expression for [tex]\( x \)[/tex]
[tex]\[ x = 7 - \frac{6}{y} \][/tex]
Substitute [tex]\( y = 2 \)[/tex]:
[tex]\[ x = 7 - \frac{6}{2} \][/tex]
[tex]\[ x = 7 - 3 \][/tex]
[tex]\[ x = 4 \][/tex]
Therefore, the solution to the system of equations is:
[tex]\[ (x, y) = (4, 2) \][/tex]
We appreciate your visit. Hopefully, the answers you found were beneficial. Don't hesitate to come back for more information. Thanks for stopping by. We strive to provide the best answers for all your questions. See you again soon. Thank you for visiting Westonci.ca, your go-to source for reliable answers. Come back soon for more expert insights.